Nationwide Outcomes of Advanced Melanoma According to BRAFV600 Status. (February 2021) - van Breeschoten, Jesper; Wouters, Michel W.J.M; de Wreede, Liesbeth C.; Hilarius, Doranne H.; Haanen, John B.; Blank, Christian U.; Aarts, Maureen J.B; van den Berkmortel, Franchette W.P.J.; de Groot, Jan-Willem B.; Hospers, Geke A.P.; Kapiteijn, Ellen; Piersma, Djura; et al.
Abstract : Objective: The aim of this study was to evaluate treatment patterns and overall survival (OS) of patients with BRAF V600 wild-type and BRAF V600 -mutant advanced melanoma in the Netherlands. Methods: We selected patients of 18 years and over, diagnosed between 2016 and 2017 with unresectable stage IIIC or IV melanoma, registered in the Dutch Melanoma Treatment Registry. To assess the association of BRAF V600 -mutation status with OS we used the Cox proportional-hazards model. Results: A total of 642 BRAF V600 wild-type and 853 mutant patients were included in the analysis. Median OS did not differ significantly between both groups, 15.2 months (95% confidence interval [CI]: 13.2-19.2) versus 20.6 months (95% CI: 18.3-25.0). Survival rates at 6 and 12 months were significantly lower for BRAF V600 wild-type patients compared with BRAF V600 -mutant patients, 72.0% (95% CI: 68.6-75.6) and 56.0% (95% CI: 52.2-60.0) versus 83.4% (95% CI: 80.9-85.9) and 65.7% (95% CI: 62.6-69.0). Two-year survival was not significantly different between both groups, 41.1% (95% CI: 37.2-45.3) versus 47.0% (95% CI: 43.6-60.6). Between 0 and 10 months, BRAF V600 wild-type patients had a decreased survival with a hazard ratio for OS of 2.00 (95% CI: 1.62-2.46) but this effect disappeared after 10 months. At 12 months, BRAF V600 -mutant patients had started with second-line systemic treatment more often compared with BRAF V600 wild-type patients (50% vs. 19%). Conclusion: These results suggest that advanced BRAF V600 wild-type melanoma patients have worse survival than BRAF V600 -mutated patients during the first 10 months after diagnosis because of less available treatment options. Abstract : Supplemental Digital Content is available in the text.